Faktor-faktor pada kejadian GAKY ibu hamil di Tabunganen Barito Kuala, Kalimantan Selatan - Alﬁ tri; Untung S. Widodo; Toto Sudargo (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2013)
ABSTRACTBackground: Iodine Deﬁ ciency Disorder (IDD) is a health problem that affects quality of human resources. IDD happens not only due to iodine deﬁ ciency but also other disorders such as goitrogenic substance (thiocyanate), pollutants of heavy metals (Pb) and micronutrient deﬁ ciency (Fe) that inhibit thyroid hormone biosynthesis which cause the sweling of goitre glands.Objective: To identify the association between consumption of iodine, thiocyanate, Fe consumption, status of anemia and Pb and status of IDD in pregnant mothers at Subdistrict of Tabunganen, District of Barito Kuala, Province of Kalimantan Selatan.Method: The study was observational using case control design and quantitative method. Data were obtained through the palpation of goitre glands, measurement of thyroid stimulating hormone (TSH) level using ELISA method, iodine and thiocyanate consumption using food recall 2x24 hours and food frequency questionnaire (FFQ), Fe consumption using FFQ, Hb level using photometric method and Pb level using AAS method. Data were analysed by using chi-square and logistic regression.Result: There was signiﬁ cant association (p<0.05) between consumption of iodine (ﬁ sh) based on FFQ and IDD status (goitre) with OR=3.44 and IDD status (TSH) with OR=8.00. There was no association between consumption of thiocyanate and Fe measured with food recall, FFQ and IDD status (goitre and TSH). There was signiﬁ cant association (p<0.05) between Pb status and IDD status (TSH) with OR=9.35.Conclusion: There was association between iodine consumption based on FFQ (ﬁ sh) and IDD status (goitre) after the control of iodine consumption status (food recall). There was association between iodine consumption status (FFQ) in ﬁ sh together with anemia status and the prevalence of IDD disorder (TSH) after the control of Pb status. KEYWORDS: iodine deﬁ ciency disorder, pregnant mothers, iodine, thiocyanate, Fe, anemia, PbABSTRAKLatar Belakang: Gangguan akibat kekurangan yodium (GAKY) merupakan masalah kesehatan yang dapat mempengaruhi kualitas sumber daya manusia. GAKY tidak hanya disebabkan oleh kekurangan yodium, tetapi juga dipengaruhi oleh zat goitrogen(tiosianat), logam berat Pb, dan kekurangan Fe yang menghambat biosintesis hormon dan berakibat pada pembesaran kelenjar gondok.Tujuan: Mengetahui hubungan antara tingkat konsumsi yodium, goitrogen (golongan tiosianat), Fe, serta status anemia dan status Pb dalam darah dengan status GAKY pada ibu hamil di  Kecamatan Tabunganen Kabupaten Barito Kuala Provinsi Kalimantan Selatan.Metode: Penelitian ini merupakan penelitian observasional dengan rancangan case control. Data pembesaran kelenjar tiroid diperiksa denganpalpasi di daerah kelenjar tiroid, kadar TSH dengan metode ELISA, tingkat konsumsi yodium dan tingkat konsumsi tiosianat dengan metode food recall 2 x 24 jam dan food frequency questionnaire  (FFQ), tingkat konsumsi Fe dengan FFQ, kadar Hb dalam darah dengan metode fotometrik, kadar Pb darah dengan metode AAS.Data dianalisis menggunakan chi-square dan logistic regression.Hasil: Ada hubungan signiﬁ kan (p<0,05) antara tingkat konsumsi yodium (ikan laut) berdasarkan FFQ dan status terhadap status GAKY (gondok) dengan OR=3,44 dan status GAKY (TSH) dengan OR=8,00.Tidak ada hubungan antara tingkat konsumsi tiosianat dan Fe yang diukur dengan food recall, FFQ, dan status GAKY (gondok dan TSH). Antara status Pb dan status GAKY (TSH) juga tidak ditemukan adanya hubungan dengan OR=9,35.Kesimpulan: Ada hubungan antara konsumsi yodium berdasarkan FFQ (ikan laut) dan status GAKY (gondok) dan antara konsumsi yodium (FFQ) dengan status anemia dan prevalensi GAKY (TSH).KATA KUNCI: gangguan akibat kekurangan yodium, wanita hamil, yodium, tiosianat, Fe, anemia, Pb